Analisa Deskriptif Google Review Untuk Mengukur Kepuasan Peserta di Kantor Cabang Lingkup Kedeputian Wilayah XII - Teguh Wijaya teguh wijaya; fanny Wiramijaya; yulisna christin (BPJS Kesehatan, 2023)
BPJS Kesehatan as a public institution mandated to organize the National Health Insurance has a big challenge related to participant satisfaction as it has entered a decade of implementing the National Health Insurance (JKN), BPJS Kesehatan is required to continue to improve satisfaction to participants, Currently, there are many ways or methods used by participants to express satisfaction or dissatisfaction with services, one of which is providing reviews through social media in the form of google reviews, related to this, researchers researched the level of participant satisfaction with BPJS Health services at branch offices throughout Deputy Region XII. This research uses descriptive research methods, namely research with an approach based on symptoms systematically and accurately regarding the characteristics of certain populations or regions, and combined with document analysis research or content analysis. The purpose of this study is to determine the level of branch office services based on the results of reviews conducted by participants through Google reviews, based on research participants who get services at the Branch Office give a rating of 4. 6 with a maximum rating scale of 5, then for the reviews given by participants, researchers categorized them according to the dimensions of the quality of participant services, namely Physical Evidence (Tangibles), Reliability, Responsiveness, Assurance, Empathy Emphaty, based on these dimensions there were 110 reviews for the July 2022-July 2023 period with the results of 106 reviews or 96.36% of participants expressing their satisfaction by giving the maximum rating of 5.